HUBUNGAN ANTARA MOTIVASI DAN EFIKASI DIRI TERHADAP KEPATUHAN CUCI TANGAN PERAWAT DI RUANG INTENSIVE RSUD TENGKU RAFIAN - Rosyadi, Imron; Lestari, Nanda Wilda (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Nosocomial infections or HAIs are the most common problems in hospitals. One of the factors that can cause the occurrence of HAIs is the non-compliance of the nurse washing hands. The purpose of this study was to determine the relationship between motivation and self-efficacy to adherence to nurses' handwashing in the intensive room of Tengku Rafian Hospital. The design of this study is descriptive correlation with a cross sectional approach. This research was conducted in the inpatient room of Tengku Rafian Hospital with a population of 52 people. The sampling technique uses a total sampling of 52 people with inclusion criteria: nurses who are on duty in the ICU, IGD, and Perinatology and have a work period of more than 3 months. The data collection tool in this study used a questionnaire and the results of the study were processed using the Chi-square test. The results in this study found that there was a significant relationship between self-efficacy of nurses' handwashing compliance in the intensive room of Tengku Rafian Hospital (p-value = 0.000) and there was no motivational relationship to nurses' handwashing compliance in the intensive room (p-value = 0.641). The suggestion from this study is that the management and the head of the nursing sector can add hand washing facilities and facilities to facilitate and increase the motivation of nurses in washing their hands at Tengku Rafian Hospital.Keywords : Motivation, Self-Efficacy, Compliance, Hand Washing